Do unilateral trade preferences help export diversification? An investigation of the impact of European unilateral trade preferences on the extensive and intensive margin of trade - Elisa Gamberoni (Graduate Institute of International Studies, 2007)
We analyze the impact of the EU unilateral trade preferences on both the intensive and the extensive margin of trade. Using a tobit and probit estimation we find that the impact of unilateral trade preferences on both margins is strictly linked to the sector under analysis and to the type of preferences a country benefits from. In particular, we find an anti-diversification effect along with a concentration of exports in agricultural products in the case of more stable preferential schemes, as represented by the African Caribbean and Pacific trade preferences. We also confirm that the Generalized System of Preferences (GSP) for least developing countries did not change the beneficiaries' export pattern, while the traditional GSP and the regime to combat drug production tend to promote diversification of exports.
Keywords: F12; F13; O19; 330; Extensive margin; Melitz model; Generalized System of Preference; Zollpräferenzen; Terms of Trade; Unvollkommener Wettbewerb; Neue Außenhandelstheorie; Schätzung; Welt